Uptake of home dialysis in younger adults: case studies that illustrate the multifaceted influence of home circumstances on dialysis decisions. Issue 12 (2nd November 2017) - Collingridge, Louise; Equinox, Keri‐Lu; Frasca, Serena; Simmonds, Rosemary; Tomlins, Melinda; Chow, Josephine
Key Clinical Message: Younger adults considering home dialysis need support to ensure home circumstances are suitable and affordable. Home circumstances relate closely to the financial burden reported by younger home dialysis users. Attention to home circumstances of younger patients with chronic kidney disease by policymakers, funders, and healthcare practitioners is needed. Abstract : Younger adults considering home dialysis need support to ensure home circumstances are suitable and affordable. Home circumstances relate closely to the financial burden reported by younger home dialysis users. Attention to home circumstances of younger patients with chronic kidney disease by policymakers, funders, and healthcare practitioners is needed.